Utility and Risk Aversion Coefficients in DSGE Models – The Case of the Czech Republic - Vérosta, Denis; Potužák, Pavel; Janíčko, Martin, 1983-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
This thesis investigates capabilities of simple real business cycle and new Keynesian models, specified with various utility function types and various values of the relative risk aversion parameter. Models are first solved for utility function of constant relative risk aversion. This serves as a benchmark for more complex utility functions such as habit formation and non-separability between consumption and hours worked. Theoretical moments of models are derived and compared to the HP filtered empirical moments of the Czech economy. It is shown that the best results were obtained for the new Keynesian model with internal habit utility function and low values of RRA = 1 and 2.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses